THE EFFECT OF TEAM WORK, LEADERSHIP STYLE, AND ORGANIZATIONAL CULTURE ON NURSE PERFORMANCE WITH ORGANIZATIONAL COMMITMENTS AS MEDIATION VARIABLES IN HOSPITAL TYPE B IN JAKARTA - Wahyuningsih, Sri Ari; Thoyib, Armanu; -, Rofiaty; Sabil, Ananda (The International Journal of Accounting and Business Society, 2019)
ABSTRACT This study aims to analyze the influence of team work, leadership style and organizational culture on nurse performance with organizational commitment as a mediating variable. The research unit is nurses at Type B hospitals in Jakarta. The population is 1362 nurses. Methods of collecting data using surveys. The research instrument used a questionnaire. Questionnaires were distributed to 523 respondents. Data analysis method uses Structural Equation Modeling-Partial Least Square SEM-PLS). The results of the study prove that teamwork has a positive effect on nurse performance. Teamwork does not affect organizational commitment. Organizational culture has a positive effect on nurse performance. Organizational culture has a positive effect on organizational commitment. Leadership style does not affect nurse performance. Leadership style does not affect organizational commitment. Organizational commitment has a positive effect on nurse performance. Organizational commitment cannot play a role in mediating the influence of teamwork on nurse performance. Organizational commitment can play a role in mediating the influence of organizational culture on nurse performance. Organizational commitment cannot play a role in mediating the influence of leadership style on nurse performance.Â  Keywords: Teamwork, Organizational Culture, Leadership Style, Organizational Commitment, Nurse Performance.